The role of religiosity in drug awareness at Women’s Rehabilitation Centers - Nisa, Wafiatun; Rahman, Imas Kania; Alkattani, Abdul Hayyi (Tawazun: Jurnal Pendidikan Islam, 2023)
This study aims to investigate the role of religiosity in the process of sensitizing drug addicts, the efforts applied in sensitization, and the factors that contribute to the increase in the number of drug addicts at Rumah Hijrah Khadijah, Bogor. This field research was conducted at Rumah Hijrah Khadijah Women’s Rehabilitation Center. Strengthening religiosity values is recognized as a means to strengthen awareness and behavior transformation. Through religious guidance, studies and lectures, compulsory and sunnah prayer guidance, dhikr, and recitation of the Qur’an, religiosity serves as a tool to guide clients in strengthening their spiritual dimension. The results showed that the role of religiosity plays a significant role in the awareness process of drug addicts in rehabilitation centers. Religiosity helps optimize efforts and guides the client’s soul in strengthening faith and piety. In this context, the role of religiosity proved to be a major supporting factor in the success of the religious approach in guiding drug addicts at Rumah Hijrah Khadijah. Abstrak Penelitian ini bertujuan untuk menginvestigasi peran religiusitas dalam proses penyadaran pecandu narkoba, upaya-upaya yang diterapkan dalam penyadaran, serta faktor-faktor yang berkontribusi pada peningkatan angka pecandu narkoba di Rumah Hijrah Khadijah, Bogor. Penelitian lapangan ini dilakukan di Panti Rehabilitasi Perempuan Rumah Hijrah Khadijah. Penguatan nilai-nilai religiusitas diakui sebagai sarana untuk memperkuat kesadaran dan transformasi perilaku. Melalui bimbingan keagamaan, kajian dan ceramah, bimbingan sholat wajib dan sunnah, dzikir, serta pembacaan Al-Qur’an, religiusitas berfungsi sebagai alat untuk membimbing para klien dalam memperkuat dimensi spiritual mereka. Hasil penelitian menunjukkan bahwa peran religiusitas berperan signifikan dalam proses penyadaran pecandu narkoba di panti rehabilitasi. Religiusitas membantu mengoptimalkan upaya dan membimbing jiwa klien dalam memperkuat iman dan ketakwaan. Dalam konteks ini, peran religiusitas terbukti sebagai faktor pendukung utama dalam keberhasilan pendekatan keagamaan dalam membimbing para pecandu narkoba di Rumah Hijrah Khadijah.